Effects of Cadmium Exposure on Lipid Peroxidation and Chlorinative Stress of Rat Kidney - Suhartono, Eko; Triawanti, Triawanti; Leksono, Amin Setyo (The Journal of Experimental Life Science, 2015)
In addition to a wide range of adverse effects on human health, toxic metals such as cadmium (Cd) can promote kidney damage. In this study, we proposed the toxicological properties of these metals which are partly related to lipid peroxidation and chlorinative stress. Thus our study aimed to measure the lipid peroxidation and chlorinative stress in kidney of rats exposed to Cd. The study was performed on 32 male rats (Rattus novergicus) weighing 300±10 grams with normal activity. Rats were acclimatized for a week before the treatment. The animals were divided into two major groups with one group for control (K0) and the other groups were exposed to 3 mg/L CdSO4 through the drinking water. The animals in each groups were divided again into two small groups with different time of exposure. The time of exposure are subacute (six weeks) and subchronic (eight weeks). After the exposure the kidney from all treated animals showed the significant increase of MDA and AOPP levels. In conclusion, subacute and subchronic exposure of Cd caused the kidney damage through lipid peroxidation and chlorinative stress, as shown by increasing of MDA and AOPP levels. Keywords: AOPP, Cadmium, Chlorinative Stress, Lipid Peroxidation, MDA